Forced swimming-induced oxytocin release into blood and brain: Effects of adrenalectomy and corticosterone treatment. (March 2017) - Torner, Luz; Plotsky, Paul M.; Neumann, Inga D.; de Jong, Trynke R.
Highlights: Adrenalectomy (ADX) caused an exaggerated secretion of OXT into the blood in response to forced swimming (FS). This exaggerated secretion was not reversed by acute i.v. or chronic s.c. corticosterone (CORT) replacement. ADX inhibited FS-induced OXT release into the paraventricular hypothalamic nucleus (PVN), which could be reversed by acute i.v. CORT infusion. These results provide a clear example of the functional separation between central and peripheral OXT release in response to stress in ADX rats. Delineating the reciprocal links between the OXT system and the HPA axis will improve our understanding of stress-related psychopathologies. Abstract: The oxytocin (OXT) system is functionally linked to the HPA axis in a reciprocal and complex manner. Certain stressors are known to cause the simultaneous release of OXT and adrenocorticotrophic hormone (ACTH) followed by corticosterone (CORT). Furthermore, brain OXT attenuates ACTH and CORT responses. Although there are some indications of CORT influencing OXT neurotransmission, specific effects of CORT on neurohypophyseal or intra-hypothalamic release of OXT have not been studied in detail. In the present set of experiments, adult male rats were adrenalectomized (ADX) or sham-operated and fitted with a jugular vein catheter and/or microdialysis probe targeting the hypothalamic paraventricular nucleus (PVN). Blood samples and dialysates were collected before and after forced swimming (FS) and analyzed for CORT, ACTH and AVP concentrations (in plasma) and OXT concentrations (in plasma and dialysates). Experimental treatments included acute infusion of CORT (70 or 175 μg/kg i.v.) 5 min prior to FS, or subcutaneous placement of 40% CORT pellets resulting in stable CORT levels in the normal basal range. Although ADX did not alter basal OXT concentrations either in plasma or in microdialysates from the PVN, it did cause an exaggerated peripheral secretion of OXT and a blunted intra-PVN release of OXT in response to FS. CORT pellets did not influence either of these ADX-induced effects, while acute infusion of 175 μg/kg CORT rescued the stress-induced rise in OXT release within the PVN and modestly increased peripheral OXT secretion. In conclusion, these results indicate that CORT regulates both peripheral and intracerebral OXT release, but in an independent manner. Whereas the peripheral secretion of OXT occurs simultaneously to HPA axis activation in response to FS and is modestly influenced by CORT, HPA axis activation and circulating CORT strongly contribute to the stress-induced stimulation of OXT release within the PVN.